PENGARUH MOTIVASI KERJA GURU, KOMPETENSI GURU DAN SUPERVISI PENGAJARAN TERHADAP PROFESIONALISME GURU SMP KATOLIK DI KOTA TOMOHON, SULAWESI UTARA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research aims to figure out the influence of Teachers‟ Work Motivation, Teachers‟ Competency, Supervision of Teaching either collectively or partially on the Teachers‟ Professionalism of Catholic Junior High Schools in Tomohon City. This research, carried out at all Catholic Junior High Schools in Tomohon City, is a quantitative research with the correlational approach. The research respondents are chosen by using technique of proportionate random sampling to the whole teachers of Catholic Junior High Schools in Tomohon City in the amount of 110 teachers. To find out the total samples, it‟s used Slovin Method and got samples in the amount of 86 teachers. The hypothesis test uses Multiple Regression Analysis. The result of this research points out that there is a positive and significant influence of Teachers‟ Work Motivation, Teachers‟ Competency, and Supervision of Teaching collectively and partially on the Professionalism of Teachers. This research finds out a large amount of effective contribution in the amount of 66,10%.